2022
DOI: 10.1186/s12931-022-02185-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of impulse oscillometry and spirometry in stable COPD and asthma

Abstract: Background While optimizing spirometry is a challenge for lung function labs, long-term variability if any between IOS (impulse oscillometry) parameters and spirometry is not clearly known in stable COPD (chronic obstructive pulmonary disease) and chronic asthma. The forced oscillation technique is increasingly employed in routine lung function testing. Our aim in this study was to determine the variability in oscillometric parameters between clinic visits over weeks or months in two patient gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Second, given the lack of information on ICS/long-acting β2-agonist (LABA) treatment, whether ICS/LABA use would affect the prognosis remained unclear. Thirdly, due to the greater variability of IOS compared with spirometric parameters [ 48 , 49 ], previous studies have reported that there was individual variability and day instability in spirometric BDR [ 3 , 50 ], however, the individual variability of IOS-BDR and whether IOS-BDR would identify a useful phenotype remained unclear. In addition, single IOS measurements was used in this study, different devices will be included to analyze the robustness of the results in future.…”
Section: Discussionmentioning
confidence: 99%
“…Second, given the lack of information on ICS/long-acting β2-agonist (LABA) treatment, whether ICS/LABA use would affect the prognosis remained unclear. Thirdly, due to the greater variability of IOS compared with spirometric parameters [ 48 , 49 ], previous studies have reported that there was individual variability and day instability in spirometric BDR [ 3 , 50 ], however, the individual variability of IOS-BDR and whether IOS-BDR would identify a useful phenotype remained unclear. In addition, single IOS measurements was used in this study, different devices will be included to analyze the robustness of the results in future.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD et asthma population, Xu et al have demonstrated that repeatability of spirometry parameters was lower than impulse oscillometry resistance parameters in different GOLD (the Global Initiative for Chronic Obstructive Lung Disease) stages, the higher the stage the worse the repeatability 13 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that viscous resistance R can sensitively detect the early stages of COPD [ 47 ]. Xu et al reported that long term variability of R 5 was correlated with stable COPD [ 48 ]. In this study, there was no correlation between PM 2.5 and X 5 .…”
Section: Discussionmentioning
confidence: 99%